1992
DOI: 10.1042/bj2850603
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of matrix metalloproteinase 9 from U937 monocytic leukaemia and HT1080 fibrosarcoma cells

Abstract: 603The precursor of matrix metalloproteinase 9 (proMMP-9), also known as '92 kDa progelatinase/type IV procollagenase', was purified from the conditioned medium of U937 monocytic leukaemia and HT1080 fibrosarcoma cell lines stimulated with phorbol 12-myristate 13-acetate. ProMMP-9 in these culture media is non-covalently complexed with the 29 kDa tissue inhibitor of metalloproteinases (TIMP), but free proMMP-9 was separated from the TIMP-proMMP-9 complex by chromatography on Green A Dyematrex gel. The final pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
7

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 29 publications
4
126
1
7
Order By: Relevance
“…Each of the resulting plasmids was transfected, together with a GFP-expressing plasmid, pCAGGS/GFP, into human fibrosarcoma cell line HT1080 and human stomach cancer line MKN28, which expressed and secreted MMP and tissue-type plasminogen activator (tPA), respectively, at high levels. 29,30 tPA has the same cleavage specificity as uPA. As shown in Figure 1c, the F protein with the cleavage motif compatible with MMP-subII was fully fusion competent in the relevant target cell line, HT1080, whereas the other three substrates (subI, subIII and subIV) were not.…”
Section: Cell-to-cell Spreading Of M Gene-deleted Sevmentioning
confidence: 99%
“…Each of the resulting plasmids was transfected, together with a GFP-expressing plasmid, pCAGGS/GFP, into human fibrosarcoma cell line HT1080 and human stomach cancer line MKN28, which expressed and secreted MMP and tissue-type plasminogen activator (tPA), respectively, at high levels. 29,30 tPA has the same cleavage specificity as uPA. As shown in Figure 1c, the F protein with the cleavage motif compatible with MMP-subII was fully fusion competent in the relevant target cell line, HT1080, whereas the other three substrates (subI, subIII and subIV) were not.…”
Section: Cell-to-cell Spreading Of M Gene-deleted Sevmentioning
confidence: 99%
“…α2-macroglobulin is an abundant plasma protein and effectively inhibits the activity of most proteinases, including the MMPs (Sottrup-Jensen and Birkedal-Hansen, 1989). Binding to α2-macroglobulin is an efficient indicator of MMP activation status as only the activated enzymes bind it (Morodomi et al, 1992). The α2-macroglobulin may play an important role in the endocytic removal of proteolytic enzymes (Moestrup et al, 1993).…”
Section: Gelatinase Inhibitors Naturally Occuring Gelatinase Inhibitorsmentioning
confidence: 99%
“…Indeed, some substrates show over 200-fold selectivity towards MMP-2 Kridel et al, 2001). (Morodomi et al, 1992;Okada et al, 1990) Native collagen type: I yes no (Aimes and Quigley, 1995) III yes no (Berton et al, 2000) IV yes yes (Morodomi et al, 1992) V yes yes (Morodomi et al, 1992) VII yes (Seltzer et al, 1989) X yes (Cole et al, 1993) XI yes (Smith et al, 1991) XVIII yes (Ferreras et al, 2000) Aggrecan yes yes (Fosang et al, 1992) BM-40/SPARC/ Osteonectin yes yes (Sasaki et al, 1997) Brevican yes no Decorin yes no (Imai et al, 1997) Elastin yes yes Entactin/nidogen no yes (Mayer et al, 1993;Sires et al, 1993) Fibrillin yes yes (Ashworth et al, 1999) Fibrin yes (Lelongt et al, 2001) Fibrinogen yes yes (Bini et al, 1996;Lelongt et al, 2001) Fibronectin yes no (Okada et al, 1990) Laminin yes yes (Giannelli et al, 1997;Morodomi et al, 1992) Link protein yes yes (Nguyen et al, 1993) NG2 proteoglycan yes (Larsen et al, 2003) Neurocan yes (Turk et al, 2001) Tenascin yes no (Siri et al, 1995) Vitronectin yes yes (Imai et al, 1995) α2-macroglobulin yes yes (Arbelaez et al, 1997) αB-crystallin yes (Starckx et al, 2003) Amyloid protein precursor yes (LePage et al, 1995) Big endothelin-1 yes yes (Fernandez-Patron et al, 2002) Calcitonin gene-related peptide (CGRP) yes (Fernandez-Patron et al, 2000) Complement protein C1q yes yes (Ruiz et al, 1999) Connective tissue-activating peptide-III (CTAP-III) yes (Van den Eph B1 tyrosine kinase receptor yes no Epithelial-cell derived neutrophil activating pept...…”
Section: Gelatinase Substratesmentioning
confidence: 99%
“…Human MMPs-1, -2, -3, and -9 were purified from human rheumatoid synovial cells and HT-1080 cells as previously described [21,22]. Preliminary experiments demonstrated that suitable conditions for collagenase digestion of C1q-CLR [2.4-4.5 mg/mL in Tris-buffered saline (TBS), pH 7.5] were achieved when incubated at 37°C for 20 h with final enzyme concentrations as follows: MMP-1 (interstitial collagenase), 1 µg/mL; MMP-2 (gelatinase A), 1.1 µg/mL; MMP-3 (stromelysin 1), 3 µg/mL; and MMP-9 (gelatinase B), 0.3 µg/mL.…”
Section: Protein Isolation Enzymatic Digestion and Biochemical Charmentioning
confidence: 99%